Hyaluronate-alginate hybrid hydrogels modified with biomimetic peptides for controlling the chondrocyte phenotype. (1st October 2018) - An, Hyoseok; Lee, Jae Won; Lee, Hyun Ji; Seo, Yerang; Park, Honghyun; Lee, Kuen Yong
Highlights: Hyaluronate-alginate hybrid (HAH) forms a hydrogel using calcium ions. HAH gel presenting biomimetic peptides has potential in tissue engineering. Precise control of cell-matrix and cell-cell interactions of HAH hydrogel is critical. Abstract: Hyaluronate-based hydrogels have been widely exploited as synthetic extracellular matrices in many tissue engineering applications, including cartilage tissue engineering. Hyaluronate-based hydrogels are typically prepared by chemical cross-linking reactions, in which chemical reagents may induce side effects, unless they are completely removed after the cross-linking reaction. We thus suggest the utilization of hybrid materials composed of hyaluronate as a main chain and alginate for physical cross-linking to simply form hydrogels in the presence of calcium ions under physiological conditions. In this study, we hypothesized that the introduction of biomimetic peptides to hyaluronate-alginate hybrid (HAH) hydrogels could be useful to regulate the chondrocyte phenotype, including chondrogenic differentiation. HAH was modified with the arginine-glycine-aspartate (RGD) peptide as a cell–matrix interaction motif and/or histidine-alanine-valine (HAV) as a cell–cell interaction motif. The HAV peptide is known to bind to cadherin, which is a key factor involved in homophilic cell–cell interactions as well as chondrogenesis. The viability and growth of mouse chondrocytes (ATDC5 cells) increased significantly when cultured on RGD-modified HAH hydrogels. Cell aggregates formed on HAV-modified HAH hydrogels, resulting in enhanced chondrogenic differentiation via enhanced cell–cell interactions by HAV modification. Interestingly, a synergistic effect of HAV and RGD peptides within HAH hydrogels on chondrogenesis was found in 3-D experiments in vitro . This approach to utilizing physically cross-linkable hyaluronate-based hydrogels presenting biomimetic peptides has potential applications in tissue engineering, including cartilage regeneration.